2015
DOI: 10.1002/ange.201505531
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Boxes: Rationally Designed Porous Organic Cages

Abstract: The porphyrin boxes (PB‐1 and PB‐2), which are rationally designed porous organic cages with a large cavity using well‐defined and rigid 3‐connected triangular and 4‐connected square shaped building units are reported. PB‐1 has a cavity as large as 1.95 nm in diameter and shows high chemical stability in a broad pH range (4.8 to 13) in aqueous media. The crystalline nature as well as cavity structure of the shape‐persistent organic cage crystals were intact even after complete removal of guest molecules, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…They have demonstrated that the interior polar hydroxyl (–OH) groups influence the CO 2 adsorption capacity of the cage. Hong and co‐workers developed wide verity of porphyrin based molecular cage and showed ∼ 200 selectivity for CO 2 separation from flue gas (CO 2 : N 2 ; 15:85 molar ratio) composition . Cooper et al .…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…They have demonstrated that the interior polar hydroxyl (–OH) groups influence the CO 2 adsorption capacity of the cage. Hong and co‐workers developed wide verity of porphyrin based molecular cage and showed ∼ 200 selectivity for CO 2 separation from flue gas (CO 2 : N 2 ; 15:85 molar ratio) composition . Cooper et al .…”
Section: Introductionsupporting
confidence: 71%
“…However, the structure and its connectivity are strongly influenced by steric groups presents to the cage vertices in the COC . In the recent years, intensive research activity has been focused on the development of COC molecules with different morphology such as tetrahedral triangular bipyramid, prismatic, prism, trigonal prismatic and prism, barrel, box and adamantoid . The structure, porosity and functional groups present in the cage influences its performance during applications.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Among the different possibilities in the design of molecular cages, the choice of metallated or freebase porphyrins leads to attractive architectures due to their chemical stability and their mimicry of natural chromophores [1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Indeed, conversion of light energy into chemical energy performed in photosynthesis relies on efficient multistep energy transfer processes between natural chromophores belonging to the family of porphyrin derivatives (chlorophyll or bacteriochlorophyll molecules) organized in antennas that convey the energy towards the reaction center where the first electron transfer step towards a free-base porphyrin derivative occurs [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Although a few examples of boronic ester cages, or those based on disulphide formation or other DCC reactions are known, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] no doubt, the vast majority of shape-persistent organic cages is relying on the use of multiple imine condensation reactions, 1 which bear the advantage to be transformed further to convert these to chemically robust cages, [27][28][29][30][31] which is for the other type of DCC reactions difficult or even impossible. 32 Among those imine cages, shapes, such as trigonal prisms, [33][34][35] tetrahedra, [36][37][38][39] truncated tetrahedra, 40,41 cubes, [42][43][44][45][46] tetrapods,…”
Section: Introductionmentioning
confidence: 99%